Age predicts peak gamma frequency and N1 amplitude of visual evoked potential - Abdullah Bin Dawood (BMC Neuroscience)
Abstract The current study investigated whether the age of healthy adults could predict the peak gamma frequency and the peak amplitudes of VEP components (N1, P2). 49 healthy participants (aged between 19 and 52 years) underwent EEG recordings during a visual task eliciting clear gamma frequency oscillations and VEP activities. After eliminating noisy and outlier data, data from 41 participants were analysed using simple linear regression. The results indicated that age was a significant predictor of peak gamma frequency and the peak amplitude of VEP-N1 but not the peak amplitude of VEP-P2. Age was negatively associated with peak gamma frequency and the peak amplitude of VEP-N1. These findings support previous research indicating that ageing is associated with decreased cortical inhibition, highlighting the importance of GABA in maintaining cortical E-I balance.